Health Examination To Student in Pesantren Baitul Qurro Jakarta. On The Pandemi Covid-19 Era - Labib, Mohammad (Program Studi Administrasi Publik)
AbstractÂ Community Service is carried out at the Baitul Qurro Islamic Boarding School, Jakarta by means of carrying out health checks. Therefore, the provision of health services targeted at school age children will be more effective if it is carried out at school. The government has launched a UKS program in schools, but so far the program's implementation has not been optimal. Purpose: This study aims to solve the problem of the health status of students and santriwan / santriwati in improving the health status of students at SMPIT and SMAIT Baitul Qurro Jakarta. Method:Systematic Random Sampling. the implementation team prepares the tools and materials used in the activity. This preparation is focused on preparing all the media and equipment needed to carry out this activity. Health checks. Activities are carried out by means of health consultations, measuring hemoglobin, checking blood pressure, Results: Health has a close relationship with learning achievement. Conclusion: The response from the level of knowledge of the school community about the UKS program was in a good category and in general there were very high expectations from the school community regarding the implementation of the UKS program.Â Keywords: Schools, Health Examination, UKS